UNICASH (CIPEEX, 2022)
THE CREATION OF UNICASH AIMS TO ENCOURAGE STUDENTS TO DELIVER ACTIVITIES IN THE AVA, €‹€‹EACH DELIVERY WOULD GENERATE A CERTAIN SCORE, WHICH CAN BE USED WITHIN UNIEVANGELICA. THE DEVELOPMENT IS BEING DEVELOPED IN MODULES, EACH DISCIPLINE GROUP WAS RESPONSIBLE FOR A PART. IT WAS DEFINED THAT EACH GROUP WILL CHOOSE IN WHICH LANGUAGE THE BACKEND WOULD BE DEVELOPED, SINCE THE FRONTEND WAS DEFINED THAT IT WOULD BE REACT NATIVE. WE WILL DEVELOP THE BASIC REGISTRATION MODULE, AT FIRST WE AIMED AT MVP, THEN WE HAD TO DEFINE WHAT WOULD BE DEVELOPED IN THE BASIC REGISTRATION MODULE, IT WAS DEFINED THAT WE WOULD HAVE LOGIN, AVA ACTIVITY DELIVERY RECORDS AND POINTS RANKING. FOR THE DEVELOPMENT OF THIS MODULE WE DECIDED THAT IT WOULD BE IN NODE WITH TYPESCRIPT AND THE DATABASE WOULD BE MAINTAINED IN SQLITE, AND WE USED THE PRISM WHICH IS A DATA UNIFIER. EVEN WITH THE DIFFICULTIES WE HAD, IT WAS POSSIBLE TO FINISH THE MVP SUCCESSFULLY.
Keywords: mvp; developed; define